2022
DOI: 10.3389/fnmol.2022.953066
|View full text |Cite
|
Sign up to set email alerts
|

S100A10 and its binding partners in depression and antidepressant actions

Abstract: S100A10 (p11) is an emerging player in the neurobiology of depression and antidepressant actions. p11 was initially thought to be a modulator of serotonin receptor (5-HTR) trafficking and serotonergic transmission, though newly identified binding partners of p11 and neurobiological studies of these proteins have shed light on multifunctional roles for p11 in the regulation of glutamatergic transmission, calcium signaling and nuclear events related to chromatin remodeling, histone modification, and gene transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 116 publications
1
8
0
Order By: Relevance
“…To test the potential of our method for investigating interaction dynamics across multiple conditions, we then utilized CRISPR-based gene knockout to perturb selected components of the 5HT 2A interaction network and to monitor resulting activation-dependent PL dynamics with the low-input PL. Our data revealed that the knockout of both, Annexin A2 (ANXA2) and S100-A10 (S100A10), two components of the 5HT 2A network, resulted in reduced biotinylation of ANXA2, S100A10, and AHNAK, which is consistent with previous findings demonstrating that these proteins physically interact (Benaud et al, 2004;Chen et al, 2022).…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…To test the potential of our method for investigating interaction dynamics across multiple conditions, we then utilized CRISPR-based gene knockout to perturb selected components of the 5HT 2A interaction network and to monitor resulting activation-dependent PL dynamics with the low-input PL. Our data revealed that the knockout of both, Annexin A2 (ANXA2) and S100-A10 (S100A10), two components of the 5HT 2A network, resulted in reduced biotinylation of ANXA2, S100A10, and AHNAK, which is consistent with previous findings demonstrating that these proteins physically interact (Benaud et al, 2004;Chen et al, 2022).…”
Section: Introductionsupporting
confidence: 92%
“…To examine how CRISPR-based KO of individual network components affects activation-dependent changes in the 5HT 2A interaction network, we selected two proximal 5HT 2A interactors from the transient cluster ( Figure 5D ), ANXA2 (Annexin A2) and S100A10 (also known as p11). S100A10 and ANXA2 form a heterotetramer (Réty et al , 1999), which has been shown to bind to membrane proteins, such as the metabotropic glutamate receptor 5 (mGluR5) (Lee et al , 2015), L-type voltage-gated calcium channel (VGCC) (Jin et al , 2020), and a subset of the 5HT receptor family (Svenningsson et al , 2006; Warner-Schmidt et al , 2009) assisting their trafficking to the plasma membrane (Chen et al , 2022). To deplete endogenous ANXA2 and S100A10 by CRISPR-Cas9 KO, two guide RNAs (gRNA) were designed per gene, complexed with Cas9 and electroporated into 5HT 2A -expressing HEK293T cells ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“… Neyazi et al (2018) assessed DNA methylation of the p11 promoter, also known as the S100A10 gene. The protein coded is multifunctional, and previous evidence suggests a link between depressive states, and response to antidepressant treatment, with peripheral p11 levels ( Chen et al, 2022 ; Gałecka et al, 2022 ). Interestingly, they found higher S100A10 promoter DNA methylation in responders to ECT.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the upregulation of PlgRKT by imipramine and serotonin, and S100A10 by citalopram and serotonin could be due to serotonin receptor signalling. There is a well-documented interaction between S100A10 and serotonin receptor expression levels and signalling in the brain (Chen et al, 2022; Sargin et al, 2020). Our current study indicates this interplay between serotonin and S100A10 also persists in non-neuronal cell lines.…”
Section: Discussionmentioning
confidence: 99%